Synthesis of a bifunctional cross-bridged chelating agent, peptide conjugation, and comparison of 68Ga labeling and complex stability characteristics with established chelators - Damerow, Helen; Wängler, Björn; Schirrmacher, Ralf; Fricker, Gert; Wängler, Carmen (ChemMedChem, 2023)
Abstract [68Ga]Ga3+ can be introduced into receptor-specific peptidic carriers via different chelators to obtain radiotracers for Positron Emission Tomography imaging and the chosen chelating agent considerably influences the in?vivo pharmacokinetics of the corresponding radiopeptides. A chelator that should be a valuable alternative to established chelating agents for 68Ga-radiolabeling of peptides would be a backbone-functionalized variant of the chelator CB-DO2A. Here, the bifunctional cross-bridged chelating agent CB-DO2A-GA was developed and compared to the established chelators DOTA, NODA-GA and DOTA-GA. For this purpose, CB-DO2A-GA(tBu)2 was introduced into the peptide Tyr3-octreotate (TATE) and in direct comparison to the corresponding DOTA-, NODA-GA-, and DOTA-GA-modified TATE analogs, CB-DO2A-GA-TATE required harsher reaction conditions for 68Ga-incorporation. Regarding the hydrophilicity profile of the resulting radiopeptides, a decrease in hydrophilicity from [68Ga]Ga-DOTA-GA-TATE (logD(7.4) of ?4.11±0.11) to [68Ga]Ga-CB-DO2A-GA-TATE (?3.02±0.08) was observed. Assessing the stability against metabolic degradation and complex challenge, [68Ga]Ga-CB-DO2A-GA demonstrated a very high kinetic inertness, exceeding that of [68Ga]Ga-DOTA-GA. Therefore, CB-DO2A-GA is a valuable alternative to established chelating agents for 68Ga-radiolabeling of peptides, especially when the formation of a very stable, positively charged 68Ga-complex is pursued.
Erstmals veröffentlicht: 19. Oktober 2022
Im Titel ist die Zahl 68 bei "68Ga" hochgestellt
Gesehen am 18.06.2024